Genome wide identification of the immunophilin gene family in Leptosphaeria maculans: a causal agent of Blackleg disease in Oilseed Rape (Brassica napus) - Singh, Khushwant; Zouhar, Miloslav; Mazakova, Jana; Rysanek, Pavel (Omics, 2014)
Abstract Phoma stem canker (blackleg) is a disease of world-wide importance on oilseed rape (Brassica napus) and can cause serious losses for crops globally. The disease is caused by dothideomycetous fungus, Leptosphaeria maculans, which is highly virulent/aggressive. Cyclophilins (CYPs) and FK506-binding proteins (FKBPs) are ubiquitous proteins belonging to the peptidyl-prolyl cis/trans isomerase (PPIase) family. They are collectively referred to as immunophilins (IMMs). In the present study, IMM genes, CYP and FKBP in haploid strain v23.1.3 of L. maculans genome, were identified and classified. Twelve CYPs and five FKBPs were determined in total. Domain architecture analysis revealed the presence of a conserved cyclophilin-like domain (CLD) in the case of CYPs and FKBP_C in the case of FKBPs. Interestingly, IMMs in L. maculans also subgrouped into single domain (SD) and multidomain (MD) proteins. They were primarily found to be localized in cytoplasm, nuclei, and mitochondria. Homologous and orthologous gene pairs were also determined by comparison with the model organism Saccharomyces cerevisiae. Remarkably, IMMs of L. maculans contain shorter introns in comparison to exons. Moreover, CYPs, in contrast with FKBPs, contain few exons. However, two CYPs were determined as being intronless. The expression profile of IMMs in both mycelium and infected primary leaves of B. napus demonstrated their potential role during infection. Secondary structure analysis revealed the presence of atypical eight β strands and two α helices fold architecture. Gene ontology analysis of IMMs predicted their significant role in protein folding and PPIase activity. Taken together, our findings for the first time present new prospects of this highly conserved gene family in phytopathogenic fungus.
Keywords: genová ontologie; Ascomycota; Gene Ontology; nemoci rostlin; Fungal Proteins; Protein Structure, Tertiary; sekvence aminokyselin; terciární struktura proteinů; Molecular Sequence Data; Genome, Fungal; Immunophilins; Amino Acid Sequence; genom fungální; Phylogeny; Brassica napus; molekulární sekvence - údaje; fungální proteiny; konzervovaná sekvence; Plant Diseases; transkriptom; Transcriptome; fylogeneze; imunofiliny; Conserved Sequence